Heuristics to Improve the BMW Method and Its Variants - Serejo de Carvalho, Lídia Lizziane; Silva de Moura, Edleno; Moura Daoud, Caio; Soares da Silva, Altigran (Journal of Information and Data Management, 2016)
In this paper, we propose and evaluate heuristics to improve the performance of BMW and its variants. The proposed changes maintain the property of preserving the order of the top ranking results, while reduce query processing times and the amount of memory required for processing queries.